Relationships between Family Support, Gender, and Education on Quality of Life in Elderly in Jambi: Multi-Level Analysis - Lestari Indah; Hanung Prasetya; Bhisma Murti (Journal of Epidemiology and Public Health, 2024)
Background: The elderly pain rate in 2021 is 22.48%, this shows that around one in five elderly people in Indonesia have experienced illness in the past month. 3 factors affect predisposing factors, including knowledge and attitudes, supporting factors, and reinforcing factors. This study aims to determine the relationship between family support, gender, and education to the quality of life of the elderly in Jambi.Subjects and Method: This was a cross-sectional study conducted in Jambi, Indonesia, from March to April 2024. A total of 200 elderly participants were selected using fixed disease sampling. The independent variables were gender, education, family support, and Integrated Health Posts for the elderly. The dependent variable is quality of life. Data were collected using questionnaires and analyzed using multiple linear regression.Results: Quality of life in old age improved with strong family support (b= 0.46; 95% CI= 0.19 to 0.74; p = 0.001) and ≥high school education (b=4.99; 95%CI = 2.89 to 7.09; p <0.0010). The quality of life of the elderly decreased or decreased in women compared to men (b= 2.94; 95% CI= -5.22 to -0.66; p= 0.011). There was a strong contextual influence of Integrated Health Posts for the elderly on the quality of life of the elderly (ICC= 31.15%).Conclusion: The quality of life of the elderly improves with strong family support and ≥high school education. The quality of life of the elderly decreases or is lower in women than men. There is a strong contextual influence of Integrated Health Posts for the elderly on the quality of life of the elderly.